Jane's world armies - Heyman, Charles (Jane's Information Group, 2000)
Jane's World Armies is an indispensable resource providing you with detailed assessments of the structure, operation and equipment of the world's armies. National inventories and procurement data are comprehensively covered country by country so that you can accurately assess threats and capabilities.